Effect of the distribution of lip-shaped matrix cracks in continuous fibre reinforced ceramic matrix composites on failure progress under transverse tension. (2nd January 2021) - Xiangping, Li; Xi, Chen; Hong, Zhang; Guangcheng, Liu
ABSTRACT: This paper develops a numerical model that contained random lip-shaped matrix cracks based on the maximum energy release rate criterion for the prediction of failure progress of Continuous Fibre-reinforced Ceramic Matrix Composites (CFCC) under transverse tension. Fibre distribution layout is created based on the actual microstructure and the Random Sequential Adsorption algorithm is used to generate the distribution of lip-shaped matrix cracks. The influence of the lip-shaped matrix crack distribution and crack density on the failure progress and stress–strain response was investigated. It was found that the onset of damage initiation commenced from the lip-shaped matrix crack when the interface fracture energy was smaller than the critical interface fracture energy. The failure progress and the predicted results were in good agreement with the experimental results. The different matrix cracks distribution affected the failure progress. Finally, the tensile strength and the elastic modulus both decreased with the crack density increasing.